The weed that strings the hangman's bag [large type] - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2010)
Flavia de Luce, a dangerously brilliant eleven-year-old with a passion for chemistry and a genius for solving murders, sets out to solve the murder of a beloved puppeteer. All clues point toward a suspicious death years earlier and a case the local constables can't solve--without Flavia's help.